Klasyfikacja powiatów według poziomu potencjału produkcyjnego rolnictwa opata na metodach analizy skupień stosowanych w genetyce - Jabłonowski, Stanisław (Poviats Classification by the Productive Capabilities of Agriculture Based on Clustering Analysis Methods Used in Genetics, 2008)
Multivariate objects linked with agriculture, like farms, rural communities etc. are classified by assorted means. The purpose of the hereto study is to check if one could transfer some taxonomic methods used in genetics into other areas, especially to agroeconomical research. Source data on which the methods are applied are electroforegrams received within PCR reaction (Polymerase Chain Reaction). In effect geneticians can estimate genetic similarities between live organisms and their populations. Agroeconomical data can be presented likewise data on an electroforegram.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 108-115